Toxoplasma gondii prevalence and risk factors in owned domestic cats from Nakhon Pathom province, Thailand - Ruenruetai Udonsom (2022)
Domestic cats are a potential source of Toxoplasma gondii infection for humans. This study was conducted to determine the seroprevalence and risk factors for T. gondii infection in domestic cats. Cat sera (n = 182) were tested for T. gondii IgG antibodies using the latex agglutination test (LAT) and the GRA7 of T. gondii (TgGRA7)-indirect enzyme-linked immunosorbent assay (iELISA). Univariable and multivariable logistic regression analyses were used to identify the factors associated with T. gondii infection. The overall prevalence rates were 18.1% (33/182) according to LAT, 19.2% (35/182) according to the iELISA and 17.0% (31/182) according to LAT and iELISA. Univariable analyses identified, outdoor access (P = 0.006), being a former stray cat (P = 0.001) and successful hunting behaviors (P = 0.04) as risk factors for T. gondii infection. Outdoor access (OR 2.63, 95% confidence interval (CI) 1.03–6.72) and is a former stray cat (OR 3.69, 95% CI 1.52–8.96) remained significant risk factors in multivariable analyses. This study indicated a relatively high seroprevalence of T. gondii among domestic cats. Cat owners can reduce the risk for T. gondii infection by not allowing their cats to roam free. Furthermore, education about the transmission of the parasite should be provided to prevent infection to the owners.